Exploring the complex interactions between microplastics and marine contaminants - Ho, Chia Min; Feng, Weiying; Li, Xiaofeng; Kalaipandian, Sundaravelpandian; Ngien, Su Kong; Yu, Xuezheng (Elsevier, 2026)
Microplastics are ubiquitous in marine ecosystems, acting as both pollutants and carriers of marine contaminants. This review synthesizes current knowledge through a comprehensive literature search (2000–2024) across Scopus, Web of Science, and PubMed, prioritizing peer-reviewed studies on interaction mechanisms, ecological impacts, and emerging co-contaminants. High surface-area-to-volume ratios, hydrophobicity, and persistent degradation resistance facilitate the accumulation and transport of diverse contaminants including persistent organic pollutants (POPs), heavy metals, pharmaceuticals and personal care products (PPCPs), and dissolved organic matter (DOM). POPs adsorb onto microplastics through hydrophobic partitioning and π–π interactions, with sorption enhanced by UV aging and biofilm. Heavy metals interact through electrostatic attraction, surface complexation, and chelation, influenced by pH, salinity, DOM, and biofilm. PPCP-microplastic interactions are mediated by hydrophobic forces, hydrogen bonding, and ion-exchange mechanisms, depending on polymer type and environmental conditions. DOM acts as both a sorbent and degradation product, with microplastics promoting DOM humification and reactive oxygen species (ROS) generation under photoirradiation. These interactions amplify ecological risks by disrupting microbial communities, promoting antibiotic resistance, and altering nutrient cycles, exacerbating climate vulnerability in coastal ecosystems per IPCC AR6 findings, with socio-economic impacts on fisheries and aquaculture, tourism, and waste management. Effective policy frameworks such as source reduction, advanced wastewater treatment, and international cooperation on plastic waste management are critical for mitigating these risks. Emerging insights into multi-pollutant interactions, including engineered nanomaterials and biotoxins, and recent technological advances for mechanistic elucidation. It underscores the importance of understanding of microplastic-contaminant interactions to mitigate ecological risks and protect marine ecosystems.